PEMBELAJARAN MENULIS TEKS PUISI DENGAN METODE CIRC PADA KELAS VIII SMPN 1 TELUK JAMBE KARAWANG - Mayasari, Diana; Wikanengsih, Wikanengsih (IKIP Siliwangi, 2019)
This class test research was conducted with the aim of increasing the creativity and ability to write poetry in Indonesian language lessons through learning with the Cooperative Integrated Reading and Composition (CIRC) method for class VIII students of BAY JAMBE 1 Junior High School in the first semester of the 2018/2019 academic year. Based on preliminary observations, it is known that the poetry writing skills of class VIII students of TELUK JAMBE KARAWANG SMPN 1 are still low and need to be improved. students still find it difficult to make creative poetry. This makes researchers want to do the research. Based on the above explanation The method used in this study is the experimental method. The results of this experiment prove that learning to write poetry using the CIRC method is effective compared to learning to write poetry without using the CIRC method